Inter-asterisk exchange (IAX) deployment scenarios in SIP-enabled networks - Boucadair, Mohamed; IEEE Xplore (Online Service); Wiley (Chichester, U.K. : Wiley, 2009)
Find out how IAX can complement SIP to overcome complications encountered in current SIP-based communications Written by an expert in the field of telecommunications, this book describes the Inter-Asterisk Exchange protocol (IAX) and its operations, discussing the main characteristics of the protocol including NAT traversal, security, IPv6 support, interworking between IPv4 and IPv6, interworking with SIP and many others. The author presents the ways in which IAX can be activated so as to avoid complications such as NAT and the presence of intermediary boxes in operational architectures. This book analytically demonstrates the added values of IAX protocol compared to existing ones, while proposing viable deployment scenarios that assess the behavior of the protocol in operational networks. Key Features: . Promotes a viable alternative protocol to ease deployment of multimedia services. Analyses the capabilities of the IAX protocol and its ability to meet VoIP service provider requirements, and provides scenarios of introducing IAX within operational architectures. Addresses the advantages and disadvantages of SIP, and Details the features of IAX that can help, in junction with SIP, to overcome various disadvantages of SIP. Explores the added values of IAX protocol compared to existing protocols. Discusses the compatibility of new adopted architectures and associated protocols This book will be a valuable reference for service providers, protocol designers, vendors and service implementers. Lecturers and advanced students computer science, electrical engineering and telecoms courses will also find this book of interest.
Further Reading -- 12 IAX and Peer-to-Peer Deployment Scenarios -- 12.1 Introduction -- 12.2 Scope -- 12.3 A P2P Solution for Corporate Customers -- 12.4 Conclusion -- References -- Further Reading -- 13 IAX and IPv6 -- 13.1 Introduction -- 13.2 Context and Assumptions -- 13.3 Service Migration to IPv6 -- 13.4 Structure -- 13.5 The IP Address Exhaustion Problem -- 13.6 IPv6: a Long-Term Solution -- 13.7 Why IPv6 May Be Problematic for Telephony Signalling Protocols: the SIP Example -- 13.8 IAX: an IP Version-Agnostic Protocol? -- 13.9 Deployment of IAX Services in a 'Pure' IPv6 Environment -- 13.10 Heterogeneous Environment -- 13.11 Conclusion -- References -- Further Reading -- 14 IAX: Towards a Lightweight SBC? -- 14.1 Introduction -- 14.2 IP Telephony Administrative Domain -- 14.3 Deployment Scenarios -- 14.4 Deployment Contexts -- 14.5 Service Limitations Caused by SBCs -- 14.6 Functional Decomposition -- 14.7 Taxonomy of SBC Functions in an SIP Environment -- 14.8 Validity of these Functions in an IAX Architecture -- 14.9 Conclusion -- References -- Further Reading -- Part Three: Deployment Scenarios in SIP-Based Environments -- 15 Scenarios for the Deployment of IAX-Based Conversational Services -- 15.1 SIP Complications -- 15.2 Structure -- 15.3 Beyond the 'SIP-Centric' Era -- 15.4 Methodology -- 15.5 Overall Context -- 15.6 Architectural Requirements -- 15.7 Brief Comparison -- 15.8 Taxonomy -- 15.9 Introducing IAX into Operational Networks -- 15.10 Conclusion. / -- References -- 16 IAX in the Access Segment of SIP-Based Service Architectures -- 16.1 Introduction -- 16.2 A 'High-Level' Description of the Interworking Function -- 16.3 Examples of Call Flows -- 16.4 Bandwidth Optimisation: An Extension to SIP -- 16.5 Conclusion -- References -- 17 Validation Scenario -- 17.1 Overview -- 17.2 Configuring Asterisk Servers -- 17.3 Configuring the SIP Express Router (SER) -- 17.4 User Agent Configuration -- 17.5 Conclusion -- Further Reading -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 10/24/2017.
Keywords: Internet telephony; Computer network protocols; Electronic books